Gynecology urography - Castillo, Jorge (2015)
As in the vaginal content, the cellular elements in it are, reflect the ovarian hormonal influences exerted in the female genital tract, and are manifested in qualitative and quantitative variations of these; well, in certain cellular elements that constitute the majority of those found in the urinary sediment, they are revealed as comparable, these gonadal influences. And this similarity, it is not only in how to react to endocrine influences, but also as or morphology; that way because they are scaly elements existing areas of epithelium in the posterior urethra and bladder trigone, especially near the internal opening of the urethra of the female urinary tract epithelium has the same plane architecture polystratified of the vagina, with its deep, medium and surface areas, wherein the cells in cylindrical -layer of germinal own deeply tórnase progressively on planes, as are closer to the surface; and similarly, the cores become small, becoming pyknotic in surface.